Taeniasis in a German Shepherd Pup: A Case Report - Thakre, BJ; Josept, Joice P; Kumar, Binod; Brahmbhatt, Nilima; Gamit, Krishna (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Taenia spp. are long, segmented, parasitic tapeworms and are relatively uncommon in canine gastrointestinal diseases compared to other tapeworms like Dipylidium caninum.